The research potential of labor, financial resources and business development of the South-Kazakhstan region - Baymuhanbetova, E; Bayneeva, P; Temirova, Zh (Journal of Economic Research & Business Administration, 2016)
Resource potential, analyzed in this paper, is presented in particu lar the potential of human resources, investments, the potential of small and medium-sized businesses in South Kazakhstan region. On the basis of these studies may identify the main factors affecting the development and use of the above types of potential. The article analyzes the dynamics of the basic indicators of regional development: Gross Regional Product by economic activity, investments in the areas and sources of financing, the structure of exports by main types of goods, the number of small and medium sized businesses, financial performance, demographics, employ ment indicators population. Based on the analysis, the authors identified a competitive advantage SKO and presents the findings of a sufficiently high resource potential of the investigated region.